[Cu(maloNHC)]-catalyzed synthesis of 2-aryl pyrazolo[5, 1-a]isoquinolines by annulation of N′-(2-((trimethylsilyl)ethynyl)benzylidene)hydrazides with terminal aromatic alkynes. Issue 45 (9th November 2017) - Liu, Huixin; Lu, Le; Hua, Ruimao
Abstract: A [Cu( malo NHC)]-catalyzed synthesis of 2-aryl pyrazolo[5, 1- a ]isoquinolines via annulation of N ′-(2-((trimethylsilyl)ethynyl)benzylidene)hydrazides with terminal aromatic alkynes was developed. Graphical abstract: